Sex-related differences of public relations managers in consumer goods companies in Greece and Italy - Panigyrakis, George G.; Veloutsou, Cleopatra A. (My University, 1998)
This paper discusses sex-related differences in Greek and Italian public relations managers comparing individual characteristics, role, level of contact and perceived quality of relations with the various interfaces, allocation of their working time, difficulties encountered and solutions proposed. The results generally support the hypothesis that there is no difference between male and female Greek and Italian public relations managers, although the issues of environmental uncertainty and role ambiguity among women in public relations requires additional research. © 1998, MCB UP Limited
Keywords: Cross-cultural management; Gender; Greece; Italy; Managers; Public relations